Результаты исследования археологического стекла из раскопа 1989 г. в историческом центре Могилёва (оптический спектральный анализ) - Синчук, И.И. (Археологія і давня історія України, 2018)
Для работы изучены 180 фрагментов стекляных
изделий из культурного слоя конца XVI — начала XX в. исторической части г. Могилева. Технологический экскурс посвящен сырью для производства стекла и знакомит с дореволюционной производственной стеклодельческой литературой. Использован метод полуколичественного оптического спектрального анализа по индексам атласа спектральных линий. Для передачи результатов используется конвенциональный общетехнический способ. 180 fragments of glassware from the historical part
of Mogilev at the end of the 16th and early 20th centuries
were studied. Technological excursus is devoted to raw materials
for glass production and introduces glassmaking literature of the 18th — early 20th centuries.
The method of semiquantitative optical spectral analysis based on the atlas of spectral lines is used. For
the transfer of results, the conventional general technical method is used. A few examples of ash glass date back to the late
of the 16th — early 17th century. Most of the samples analyzed from the 17th to the 19th centuries are made
of potassium-calcium silicate glass; about 1/3 part of the products, there are manganese impurities, which
makes the glass colorless. The result of the work is a catalog of analyzes of an
archaeological glass from the Belarusian city of Mogilev, which presented in the appendix.